Bereavement-Associated Psychotic Depression in a Patient with Hyperthyroidism: A Case Report - Kamila Aisyah; Era Catur Prasetya (CV. CENDIKIA JENIUS INDONESIA, 2025)
Psychotic depression is a severe and complex mood disorder with a high risk of morbidity, particularly when triggered by psychosocial stressors such as bereavement and worsened by medical comorbidities like hyperthyroidism. This study aims to describe clinically the interaction between psychosocial, biological, and medical factors in a case of bereavement-associated psychotic depression. A descriptive case study with a prospective approach was conducted on a 46-year-old female outpatient at the Psychiatric Clinic of Muhammadiyah Lamongan Hospital on September 30, 2025. Data were collected through in-depth interviews, mental status examination, and behavioral observation, and analyzed qualitatively. The patient presented with severe depressive symptoms, mood-congruent auditory hallucinations, bereavement stress, and hyperthyroidism aggravating her emotional instability. The diagnosis was *Major Depressive Disorder* with mood-congruent psychotic features, treated with a combination of antidepressants, antipsychotics, hyperthyroidism management, supportive psychotherapy, and family psychoeducation. In conclusion, this case highlights the importance of a biopsychosocial approach in diagnosing and managing psychotic depression with medical comorbidities. Mental health professionals are encouraged to perform comprehensive screening for biological factors and psychosocial stressors to optimize patient outcomes.